ANALYSIS OF RELATIONSHIP SCIENCE PROCESS SKILLS AND CREATIVITY WITH THE COGNITIVE LEARNING OUTCOMES USED OF THE ICARE PRACTICE BASED ON WORKSHEET ON LEARNING HIGH SCHOOL PHYSICS COURSES - Jurubahasa Sinuraya; Deo Demonta Panggabean; Ida Wahyuni (Universitas Negeri Medan, 2019)
The research aims to determine the relationship between creativity and cognitive learning outcomes through the use of The ICARE Practice Based on Worksheet. This type of research is experimental research. The subjects of this study were 34 students who took high school physics courses in Physics Education Study Program majoring in physics, mathematics and natural sciences faculty, Medan State University. Data on student creativity was taken through the 3 item test validation test instrument that has been validated. Cognitive learning outcome data obtained through multiple-choice test instruments as many as 25 items that have been validated. The data analysis technique used is multiple regression. The results of the analysis for the coefficient of determination (R2) of 0.472 indicate that 47.20% of learning outcomes are influenced by science process skills and creativity.